Where are we with bladder preservation for muscle-invasive bladder cancer in 2017? - Smelser, Woodson Wade (Indian J Urol, 2017)
INTRODUCTION: In 2017, neoadjuvant, cisplatin-based chemotherapy followed by radical cystectomy (RC) is considered the gold standard therapy for muscle-invasive bladder based on randomized controlled trials. Across all tumor stages, this approach has been associated with the highest rates of disease-specific survival. However, RC is one of the most challenging procedures performed by urologic surgeons and carries with it significant risks of complications, hospital readmission, and even a small risk of mortality, in addition to lifestyle changes that can have long-term effects on well-being. For these reasons, bladder-sparing approaches are utilized in some highly selected patients. We reviewed the most recent evidence for bladder-sparing modalities for muscle-invasive urothelial bladder cancer and summarize those findings in this review article. METHODS: We performed a PubMed literature review utilizing the key words “bladder preservation,” “trimodal therapy,” “muscle-invasive bladder cancer,” and “partial cystectomy” written in English, dating back to 1990. We excluded case reports. RESULTS: Our search yielded more than 2000 articles which we screened. Some articles were then rejected due to inappropriate topic. In addition, we reviewed the most recent American Urological Association, National Comprehensive Cancer Network (NCCN), and European guidelines on muscle-invasive bladder cancer. We identified fifty relevant articles which are summarized in this text. In some rare instances, recommendations are based on expert opinion. CONCLUSIONS: Bladder preservation is often considered for quality of life considerations or in the setting of multiple medical comorbidities, and this remains oncologically appropriate even in 2016 in highly selected patients with muscle-invasive urothelial carcinoma of the bladder.